Epitaxial growth of non-polar a-plane ZnO and aluminium-doped ZnO on r-sapphire using the intermittent spray pyrolysis methodology - Cerine Treesa Russel; Carmen Martinez Tomas; Vicente Muñoz Sanjosé (Applied Surface Science Advances)
In this article, we highlight the epitaxial growth of non-polar a-plane ZnO and aluminium-doped ZnO using the low-cost, non-vacuum and highly up-scalable intermittent spray pyrolysis technique. We successfully deposited epitaxial ZnO and Al: ZnO thin films over r-sapphire using our optimized homemade Spray Pyrolysis setup. The epitaxial relationships are those usually found in the samples grown by the conventional well established epitaxial growth methods, that is, with a ZnO(112¯0)∥Al2O3(011¯2) out-of-plane direction. We investigated the effect of growth temperature on the growth of ZnO over r-sapphire substrate in the temperature range 300 °C to 600 °C and found that under the growth conditions that were used, there was an optimum growth temperature range of 450 °C-500 °C in which we could grow very compact uniform epitaxial ZnO thin films. At both, lower and higher growth temperatures, due to the instability induced in growth conditions (Ehrlich-Schwoebel effect and stress-induced instability, respectively), there was surface roughening. The effect of aluminium doping on ZnO was also investigated for the optimum growth temperatures 450 °C and 500 °C using morphological, structural and electrical (Hall measurements) characterisation. The Al:ZnO sample with a nominal aluminium concentration of 1 % without any post-deposition treatments had a carrier concentration of 5.03 × 1019 cm-3 and mobility of 10 cm2/V·s.